Evaluation of 12 Bread Wheat Varieties for Seed Yield and Some Chemical Properties Grown in Northwestern Turkey - TAYYAR, SEMUN; KEMAL GUL, M. (Asian Journal of Chemistry, 2010)
The quality and yield of wheat grain have been increasingly becoming an important factor in cereal trading throughout the world. Breeders have to make many efforts to breed new cultivars giving more yields with high quality. In this research, grain yield, some agronomic characteristics (spike length, number of spikelets, number of grain per spike, grain weight per spike, harvest index, 1000 grain weight and plant height) and quality traits (hectoliter weight, grain moisture, protein, ash, falling number, gluten, gluten index, sedimentation and modified sedimentation) of 12 bread wheat varieties grown during the growing seasons of 2004-2005 and 2005-2006 were investigated. The purpose of the study was to determine the performances and some chemical compositions related to flour quality of different bread wheat genotypes under the ecological conditions of Biga, located in the northwest part of Turkey and to investigate the correlations among quality parameters. Significant differences for all important traits; yield (4064.7- 6141.5 kg ha-1), protein content (10.63-13.18 %), gluten content (28.97- 37.43 %) and gluten index (54.50-94.00 %) were found. High and positive correlations were observed between protein content and some other quality traits (ash, falling number, gluten, sedimentation and modified sedimentation). Tosunbey was the best variety with high yield and quality parameters.